Integration of porous low-k dielectrics using post porosity pore protection. (17th November 2016) - Zhang, Liping; de Marneffe, Jean-François; Verdonck, Patrick; Heylen, Nancy; Wen, Liang Gong; Wilson, Chris; Tokei, Zsolt; Boemmels, Juergen; De Gendt, Stefan; Baklanov, Mikhail R
Abstract: Post porosity pore protection is studied as a means for low damage integration of porous low- k dielectrics. Homogeneous low- k densification is achieved using poly(methyl methacrylate) (PMMA) as a sacrificial filler. The improvement in plasma-induced damage is investigated on a plasma-enhanced chemical vapor deposition 2.0 porous organo-silicate glass, including damage from radicals and vacuum ultraviolet photons. Open pores are sealed upon polymer protection; therefore the penetration of metal species during deposition of a metal diffusion barrier is avoided. Various solutions for post metallization polymer removal are investigated, such as hydrogen remote plasma and an ultraviolet cure. The PMMA removal process is studied in order to avoid Cu wire degradation. Finally, low- k damage and barrier continuity are investigated on patterned wafers with functional circuits. By means of transmission electron microscopy inspection and electrical measurement, effective integrated k -values are extracted, giving a value k eff ~ 2.5–2.6 for the post metallization polymer removal option.